Prevalence and nature of workplace harassment among class-IV employees in public hospitals of Lahore, Pakistan: a cross-sectional study - Muhammad Shahzad; Mehwish Nawaz; Saqlain Ghazanfar; Abdur Rehman; Muhammad Hamza Raees; Ali Hassan Ranjha (Discover Public Health)
Abstract Background Workplace harassment is a pervasive issue in healthcare, with lower-status employees often being the most vulnerable. While healthcare professionals such as doctors and nurses have received considerable attention in harassment studies, class-IV employees, who provide essential but lower-status services, remain underexplored. Aim This study aimed to assess the prevalence and types of workplace harassment experienced by class-IV employees in public hospitals in Lahore, Pakistan. Methods A cross-sectional study was conducted among 358 class-IV employees across three public hospitals in Lahore. Data were collected using the Negative Acts Questionnaire-Revised (NAQ-R), which measures exposure to workplace harassment. The sample included sanitary workers, security guards, ward attendants, and other essential service providers. Demographic and harassment data were analyzed using descriptive statistics, Chi-square tests, and ANOVA. Results The majority of participants were male (72.9%), married (85.5%), and illiterate (53.1%). Overall, 9.2% reported occasional harassment, while 0.3% experienced severe harassment. Work-related harassment was the most common (17.5%), followed by physically intimidating (12.5%) and person-related harassment (4.3%). Sanitary workers were disproportionately affected (15.7% vs. 5.5% in other roles, p = 0.001). Post-hoc analyses revealed significant differences in harassment levels across job categories, with sanitary workers experiencing the highest levels. Conclusion Sanitary workers reported a higher risk for work-related harassment in public hospitals. These findings underscore the need for targeted interventions and policy reforms to protect vulnerable healthcare workers from mistreatment, improve working conditions, and promote a culture of respect and safety in healthcare settings.